CLASSROOM INTERACTION IN ENGLISH LESSON THROUGH FLANDER’S INTERACTION ANALYSIS CATEGORIES SYSTEM (FIACS) AT THE ELEVENTH GRADE OF MANDIRI VOCATIONAL SCHOOL - Endang Pratiwi Marbun; Anni Holila Pulungan (Universitas Negeri Medan, 2017)
This study focuces on analyzing the process of classroom interaction through Flanders Interaction Analysis Category (FIAC) model. The objective was to describe how the teacher and students use the categories of classroom interaction in English class by using Flanders Interaction Analysis Category (FIAC) model. The data is found based on the data transcription. The source of the data were the English teacher and 11th grade students at Vocational School Mandiri Percut Sei Tuan. The instruments for data collection were observation, video recording, and note talking. The design of data analysis applied descriptive qualitative design. In analyzing the data, the researcher dentifying the data transcription, Classifying the data, Giving a code number, pairing the data, and Plotting the code number into a matrix. It was found that the total percentage each categories classroom interaction were accepts feelings (2.15%), praise and encourages (9.67%), accepts or uses the ideas of the students (0%), asks questions (18.27%), lecturing (6.45%), giving directions (15.05%), criticizingor justifying authority (12.90%), students talk-response (32.25%), students talk-initiation (2.15%), and silence or confusion (1.07%). It showed the students participated in the interaction process.